Interneuron hyperexcitability as both causal factor and risk factor in Alzheimer's disease: Molecular and cell biology/others. (7th December 2020) - Hijazi, Sara; Heistek, Tim; Scheltens, Philip; Mansvelder, Huibert D.; Smit, August B.; van Kesteren, Ronald E.
Abstract: Background: Neuronal network dysfunction is increasingly recognized as an early sign of Alzheimer's disease (AD). This is seen for instance as neuronal hyperexcitability, a disturbance of excitation/inhibition balance and altered oscillatory activity and synchrony, both in patients and in mouse models of AD. The causes and functional implications of these network alterations are currently only starting to be revealed. Methods: We tested the contribution of hippocampal parvalbumin‐positive interneurons to early neuronal network dysfunction in an APP/PS1 mouse model of AD. Patch clamp analysis was performed to measure neuronal excitability and synaptic connectivity. Chemogenetics was used to specifically restore PV cell excitability in APP/PS1 mice, or induce PV cell hyperexcitability in wildtype mice. A Morris water maze test was used to determine the consequences of these manipulations for learning and memory. Results: We found that hippocampal PV interneurons become hyperexcitable in APP/PS1 mice at an early disease stage, at 3‐4 months of age. Reducing PV cell excitability restores neuronal network properties and rescues learning and memory deficits. These effects are long‐lasting and are paralleled by a significant reduction in soluble amyloid‐beta concentrations and amyloid plaque load. Conversely, when we chemogenetically induced PV cell hyperexcitability in wildtype mice, animals developed network dysfunction and learning and memory impairments similar as observed in APP/PS1 mice. Interestingly, these impairments were transient, but could be reinstated by a singly low‐dose injection of amyloid‐beta directly into the hippocampus. Conclusion: Hippocampal PV interneuron hyperexcitability is an early phenomenon in APP/PS1 mice and causally contributes to the development of other AD‐like symptoms, such as neuronal network dysfunction, cognitive impairment and amyloid pathology. Interestingly, hyperexcitable PV neurons also renders healthy hippocampal circuitry vulnerable to amyloid‐beta‐induced toxicity. These findings thus establish PV cell hyperexcitability as both a causal factor and a risk factor in AD.